Opinion and Special Articles: Cerebellar Ataxia and Liver Failure Complicating IPEX Syndrome. (9th February 2021) - Rim, Joshua; Byler, Melissa; Soldatos, Ariane; Notarangelo, Luigi; Leibovitch, Emily; Jacobson, Steven; Gorman, Mark; Lebel, Robert Roger; Werner, Klaus
Abstract : Immunodysregulation, polyendocrinopathy, and enteropathy, X-linked (IPEX) syndrome is an autoimmune condition caused by mutations in the Forkhead Box P3 ( FOXP3 ) gene, which maps to chromosome Xp11.23 (OMIM #304790). 1 It typically presents within the first year of life with watery diarrhea, eczematous dermatitis, and endocrinopathy (most commonly diabetes mellitus). 1 Most children have other autoimmune phenomena including Coombs-positive anemia, thrombocytopenia, neutropenia, and tubular nephropathy. 1 Bone marrow transplantation is the only definitive cure for IPEX syndrome. 2 Neurologic involvement in IPEX syndrome has not been well characterized in the literature, based on a current Ovid MEDLINE search. Without aggressive immunosuppression or bone marrow transplantation, the majority of affected boys die within the first 1 to 2 years of life from metabolic derangements or sepsis. 1 Diagnosis is based on clinical features and whole exome sequencing that reveals a pathogenic FOXP3 variant. 1